FORMATION OF AN EFFECTIVE HUMAN RIGHTS PROTECTION SYSTEM IN UKRAINE AND SWEDEN: A COMPARATIVE ASPECT - Cherevatiuk, Viktoriya; Cherevatiuk, Alina (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
The purpose of this article is to find out the individual components necessary for the formation of an effective human rights protection system in Ukraine, using the experience of Sweden. Methods: to achieve the defined goal, general and special scientific methods were used, in particular, dialectical, axiological, objectivity, systematic, analysis, and comparative legal methods, which ensured the integrity of the research and the determination of directions for the formation of an effective mechanism for the protection of human rights. Results: the formation of an effective human rights protection system in Ukraine is closely related to the rejection of the positivist interpretation of human rights and the adoption of a natural-law approach, according to which human rights derive from human nature and are therefore essential. Discussion: using, among other things, the experience of Sweden in the protection of human rights, which involves a combination of the legal framework, institutional mechanisms, the participation of civil society in the protection of human rights and international cooperation, Ukraine can form an effective system for the protection of human rights, integrating all the necessary components: legislative support, independent judiciary, developed civil society, the development of a culture of respect for human rights, international cooperation, innovative approaches to ensuring and protecting human rights, etc. Effective protection of human rights in Ukraine is possible only under the condition of the functioning of a developed civil society.